2002
DOI: 10.1093/gerona/57.11.m733
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nurse Counseling on Walking for Exercise in Elderly Primary Care Patients

Abstract: Background. Counseling sedentary primary care patients can increase physical activity, but whether this approach will increase exercise and fitness in elderly adults with chronic diseases remains to be determined. Methods. After receiving individualized nurse counseling to begin a program of walking for health, 60- to 80-year-old primary care patients were randomized to one of three levels of telephone contacts over 10 months: (i) 20 nurse-initiated calls, (ii) 10 nurse-initiated calls plus 10 motivational cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(112 citation statements)
references
References 26 publications
4
108
0
Order By: Relevance
“…Consequently, for those attending formal exercise classes who are expected to continue these at home, ongoing group activities after these have terminated are indicated (McKelvie et al, 2002). Similarly, the importance of having an exercise companion (Dubbert, Cooper, Kirchner, Meydrech, & Bilbrew, 2002) and ongoing contacts with an empathetic professional have been stressed (KeeleSmith & Leon, 2003;Marks, 1994). Investigative work by Mazzucca et al (1997) has further suggested that in the context of knee osteoarthritis, sustained preservation of function and consistent effects of exercise on pain relief might require prolonged, proactive follow-up of patients by either a patient educator or a trained clinical assistant.…”
Section: Methods Of Fostering Exercise Adherencementioning
confidence: 99%
“…Consequently, for those attending formal exercise classes who are expected to continue these at home, ongoing group activities after these have terminated are indicated (McKelvie et al, 2002). Similarly, the importance of having an exercise companion (Dubbert, Cooper, Kirchner, Meydrech, & Bilbrew, 2002) and ongoing contacts with an empathetic professional have been stressed (KeeleSmith & Leon, 2003;Marks, 1994). Investigative work by Mazzucca et al (1997) has further suggested that in the context of knee osteoarthritis, sustained preservation of function and consistent effects of exercise on pain relief might require prolonged, proactive follow-up of patients by either a patient educator or a trained clinical assistant.…”
Section: Methods Of Fostering Exercise Adherencementioning
confidence: 99%
“…Three of these studies concluded that more intensive intervention was required to increase physical activity [20,22,23]. Aerobic fitness was only assessed in three studies [17,24,25]. A high-quality study reported maximal oxygen uptake (VO 2 max) improvements of 14% among EoP patients and 3% among controls after 12 months (11% and 4% after six months) [24].…”
Section: Effect Of Exercise On Prescriptionmentioning
confidence: 99%
“…Fifteen studies on advice or counseling fulfilling the criteria were identified [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. They were all conducted in primary care settings with patients by ordinary health care professionals.…”
Section: Promotion Of Physical Activity In Health Care: Results From mentioning
confidence: 99%